Pelatihan Penggunaan Literasi Digital Untuk Menunjang Pendidikan Dan Umkm - Khaerudin, Muhammad; Tukino; Ratna Juwita, Ayu; Rohana, Tatang; Winarni (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
The pandemic conditions have opened up opportunities for teenagers to do business. In conditions like this, it is hoped that teenagers can use their time positively and productively. Mental readiness and skills need to be prepared before someone enters the world of work. Meanwhile, applications in the field of information technology have a big impact in various areas of life, one of which is in the creative industry such as advertising, billboards, graphic design and digital image processing. One of them is supporting skills for the younger generation. The method of community service carried out by a team of lecturers at Bhayangkara University, Greater Jakarta this time is in the form of training in graphic design skills using computers and using CorelDraw and Photoshop software. This activity aims to increase the knowledge and skills of youth in improving the quality of their abilities in creating attractive graphic designs so that participants can compete to meet the demand for employment and also towards entrepreneurship. The training given to participants includes creating and completing product designs for advertising or printing needs. The results of graphic design skills training activities show that participants can design logos, business cards, invitations, leaflets, banners and other forms of advertising.